Saintly Models and Lifestyles in the Sociological Tradition - Luigi Berzano (Ocula)
This text intends to formulate a hypothesis of holiness as a daily lifestyle. The first point, The transcendent sacred, when introducing the three above-mentioned classics, is a common reference to the idea of the sacred as a transcendent reality of the individual at moments and during experiences of great religious intensity, albeit reserved exclusively to the administration of religious institutions. The second point, The daily-life sacred, refers to less intense forms of the sacred, different for each individual, which are discovered and constructed through personal vicissitudes and therefore 'sustainable' by everyday life. The third point, Transcendent holiness, deals with heroic, exceptional models of holiness proposed to its faithful by the Church. The fourth point, Holiness in daily life, forms a model of holiness of all the faithful representing professions, jobs, cultures and diverse sensibilities. The conclusion, From heroic saints to sustainable models of holiness, formulates two fields of future research: relations between models of sanctity and sociocultural, economic and ecclesiastical contexts; and the progressive power of the papacy in controlling and declaring holiness.